2016
DOI: 10.1039/c5cc09158f
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of BiOClxBr1−x/alumina composite films with highly exposed {001} facets and their superior photocatalytic activities

Abstract: We report the fabrication of thin films of bismuth oxyhalide solid solution with highly exposed {001} facets with the help of cetyltrimethylammonium bromide and aluminium oxyhydroxide. These {001} facet exposed films showed enhanced photocatalytic activities compared to those of randomly oriented facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In addition, as compared to those were prepared by solution technique (denoted as BiOCl 1‐ x Br x solution) (Figure a) , it could be found that the intensity ratios of the peaks (110) to (101) herein are obviously increased, which imply that growth orientation of the BiOCl 1‐ x Br x obtained herein is [110]. And so, the mainly exposed facets may be {001} facets . Furthermore, the diffraction peaks of the as‐prepared BiOCl 1‐ x Br x became wider as compared to those obtained by solution method, which should be caused by the decrease in particles size, the replacement of Clˉ ions by Brˉ ions and low crystallinity due to nonsolvent crystallization.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, as compared to those were prepared by solution technique (denoted as BiOCl 1‐ x Br x solution) (Figure a) , it could be found that the intensity ratios of the peaks (110) to (101) herein are obviously increased, which imply that growth orientation of the BiOCl 1‐ x Br x obtained herein is [110]. And so, the mainly exposed facets may be {001} facets . Furthermore, the diffraction peaks of the as‐prepared BiOCl 1‐ x Br x became wider as compared to those obtained by solution method, which should be caused by the decrease in particles size, the replacement of Clˉ ions by Brˉ ions and low crystallinity due to nonsolvent crystallization.…”
Section: Resultsmentioning
confidence: 88%
“…The {001} facets of the layered bismuth oxyhalides are theoretically considered to be the most favorable facets to photocatalytic reactivity owing to the extremely high thermodynamic stability and low electron–hole recombination rate. For example, Dandapat's group reported that BiOCl x Br 1− x with highly exposed {001} facets showed high photoactivity . Jiang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth oxyhalides (BiOX) have attracted great interest for their potentials in heterogeneous catalysis, photocatalysis, pigments, nanodevices and nanosensors . Due to strong intralayer covalent bonding and weak interlayer van der Walls interaction, BiOX possess highly anisotropic structural, optical, electronic as well as mechanical properties.…”
Section: Figurementioning
confidence: 99%
“…Using BiOCl nanoplates, Zhang et al demonstrated air purification by elimination of NO under visible‐light irradiation. Recently, Gnayem et al fabricated microspherical heterostructure of BiOCl x Br 1–x and demonstrated its excellent photocatalytic activity under 422 nm light irradiation to clean chemical waste from water. The above discussed experiments for waste water treatment or air purification are performed using BiOCl powder samples at small scale.…”
Section: Introductionmentioning
confidence: 99%
“…They compared BiOCl nanosheet arrays and P25 (TiO 2 ) film by MO degradation under UV irradiation and confirmed better durability and degradation rate for BiOCl. Making of BiOCl x Br 1‐x /alumina composite films through hydrothermal is reported by the group of Yoel Sasson and their co‐workers . Recently, Li et al fabricated the film accompanied with nanoflakes of BiOCl over stainless steel (SS) substrate showing super hydrophobicity for water drop.…”
Section: Introductionmentioning
confidence: 99%